Efficiency and costs of payments: some new evidence from Finland - Kari Takala; Matti Virén (Bank of Finland, 2008)
This paper deals with optimal payment systems. The issue boils down to how large are the costs of different payment media, which can be interpreted as a question of the efficiency of the means of payment. However, there are other qualifications related to the choice of payment media. Here, at least three issues can be distinguished. First is the question of optimal payment medium for each individual payment (size, location, EFTPOS etc.). This choice is not independent of the individual characteristics of the payer and payee. Secondly, there is the question of cost effectiveness of payments for different institutions and sectors. The final issue concerns the social optimum for each payment medium. These issues have been particularly controversial in the case of cash, which is still the dominant payment medium in most euro countries. Part of the controversy arises from the fact that the costs and benefits of different payment media affect different market participants in quite different ways, so that a possible social optimum might not correspond eg to the optima for different firms. The paper contains a short review of calculation methods and empirical results for a sample of countries. It also provides new evidence from Finland, which is to an extent one of the front-runners in payment technology and institutional design in payment systems. This shows up in relatively low overall costs of payments. Our estimate of total costs of payment media is 0.3 per cent of GDP, which is very low by international standards.
URN:NBN:fi:bof-20140807253
Keywords: 330